Associations of serum sex steroid hormones and 5α-androstane-3α,17β-diol glucuronide concentrations with prostate cancer risk among men treated with finasteride - Kristal, Alan R. (2012)
BACKGROUND: Finasteride, an inhibitor of 5 α-reductase (Type II), lowers intraprostatic dihydrotestosterone (DHT), which is reflected in serum as reduced 5α-androstane-3α,17β-diol glucuronide (3α-dG). It also modestly increases serum testosterone (T), estrone (E1) and estradiol (E2). In this altered hormonal milieu, it is unknown whether serum concentrations of these hormones are associated with prostate cancer risk. METHODS: In this nested case-control study of men in the finasteride arm of the Prostate Cancer Prevention Trial, sex steroid hormones and sex hormone binding globulin (SHBG) were measured at baseline and approximately 3-years post-treatment in 553 prostate cancer cases and 694 controls. RESULTS: Median post-treatment changes in concentrations of 3α-dG, T, E1, and E2 were −73.8%, +10.1%, +11.2%, and +7.5% (all p<0.001), respectively. Neither the pre- nor post-treatment concentrations of 3α-dG, nor its change, were associated with risk. Pre-treatment, high concentrations of E1 and low concentrations of T were associated with increased cancer risk (Odds Ratio[95% CI] quartile 4 vs 1: 1.38[0.99–1.93] ptrend=0.03; 0.64 [0.43–0.93] ptrend=0.07, respectively). Post-treatment, high concentrations of both E1 and E2 and were associated with increased cancer risk (OR[95% CI] quartile 4 vs 1: 1.54[1.09–2.17] ptrend=0.03; 1.49[1.07–2.07] ptrend=0.02, respectively). CONCLUSIONS: Among finasteride-treated men, concentrations of 3α-dG were not associated with total or Gleason grades 2–6, 7–10 or 8–10 cancer. High serum estrogens may increase cancer risk when intraprostatic DHT is pharmacologically lowered. IMPACT: Low post-treatment serum estrogens may identify men more likely to benefit from use of finasteride to prevent prostate cancer.